A Review of the Impact of Streptococcal Infections and Antimicrobial Resistance on Human Health - Raina Gergova; Vasil Boyanov; Adile Muhtarova; Alexandra Alexandrova (MDPI AG, 2024)
Streptococcus pneumoniae, Streptococcus pyogenes (GAS), and Streptococcus agalactiae (GBS) are bacteria that can cause a range of infections, some of them life-threatening. This review examines the spread of antibiotic resistance and its mechanisms against antibiotics for streptococcal infections. Data on high-level penicillin-resistant invasive pneumococci have been found in Brazil (42.8%) and Japan (77%). The resistance is caused by mutations in genes that encode penicillin-binding proteins. Similarly, GAS and GBS strains reported from Asia, the USA, and Africa have undergone similar transformations in PBPs. Resistance to major alternatives of penicillins, macrolides, and lincosamides has become widespread among pneumococci and streptococci, especially in Asia (70-95%). The combination of several emm types with erm(B) is associated with the development of high-level macrolide resistance in GAS. Major mechanisms are ribosomal target modifications encoded by erm genes, ribosomal alterations, and active efflux pumps that regulate antibiotic entry due to mefA/E and msrD genes. Tetracycline resistance for streptococci in different countries varied from 22.4% in the USA to 83.7/100% in China, due to tet genes. Combined tetracycline/macrolide resistance is usually linked with the insertion of ermB into the transposon carrying tetM. New quinolone resistance is increasing by between 11.5 and 47.9% in Asia and Europe. The mechanism of quinolone resistance is based on mutations in gyrA/B, determinants for DNA gyrase, or parC/E encoding topoisomerase IV. The results for antibiotic resistance are alarming, and urgently call for increased monitoring of this problem and precautionary measures for control to prevent the spread of resistant mutant strains.